Successful treatment of generalized myasthenia gravis with telitacicept: a Chinese case series and literature review - Xiaodong Song; Xiaodong Song; Yang He; Hong Jiang; Yao Yu; Yue Sun; Zhaoxu Zhang (Frontiers in Neurology)
BackgroundDespite existing treatments of generalized myasthenia gravis (gMG), there remains a need for more effective therapies with fewer side effects. Telitacicept, targeting B lymphocyte stimulator (BLyS) and a proliferation-inducing ligand (APRIL), emerges as a potential novel therapy for gMG.Case presentationIn our study, four patients with gMG to standard treatments underwent an 8-week course of telitacicept monotherapy. Post-treatment, all patients exhibited satisfactory improvements. The Myasthenia Gravis Foundation of America Quantitative Myasthenia Gravis (MGFA-QMG) scores, 15-item Myasthenia Gravis Quality of Life (MGQOL-15) scores, and MG-associated Activities of Daily Living (MG-ADL) scores showed a marked reduction, indicating decreased disease severity and enhanced quality of life. Additionally, immunological assessments revealed a decrease in CD19+B lymphocyte counts and acetylcholine receptor (AChR) antibodies. Only one patient reported a mild, transient injection reaction.ConclusionFavorable clinical improvement and mild adverse events for gMG in treated with telitacicept were observed. However, larger-scale and longer-term studies are necessary to confirm these results and fully establish the role of telitacicept in the treatment of gMG.